PILOT STUDY OF SELF-ORGANIZATION AND THE FORMATION OF SOCIAL AND PEDAGOGICAL COMPETENCIES IN THE EDUCATIONAL ACTIVITIES OF STUDENTS - Kosshygulova, Aliya; Sadykova, Anel (Pedagogy and Psychology, 2021)
The article is devoted to the problem of psychological analysis of self-organization in the educational activities of modern students. Self-organization is the central link arising in the development of social and pedagogical competencies. The article discusses a pilot study of the criteria for the formation of self-organization and current methods of their study in the framework of socio-pedagogical competencies. Trends in the development of modern higher education are due to the global processes of integration of the world educational system, digitalization of the educational space, increased requirements for the quality of training specialists in a highly competitive labor market. Informatization, broad opportunities for obtaining knowledge, and involvement in the global educational process can benefit the subject of educational activity only if they possess the skills of self-organization, planning and self-control of activities.